ВЛИЯНИЕ ЦИФРОВЫХ ЭКОСИСТЕМ НА РАЗВИТИЕ МЕЖДУНАРОДНОГО БИЗНЕСА АКЦИОНЕРНЫХ ОБЩЕСТВ КОРПОРАТИВНЫХ КОМПАНИЙ - Турдымуратова Азиза Кыясовна (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines the role of digital ecosystems in transforming the international activities of joint-stock companies. The mechanisms through which digitalization impacts operational efficiency, risk management, market expansion, and competitiveness are explored. Successful case studies of leading corporations are analyzed to identify strategies for integrating digital platforms into global business processes. Recommendations are provided on leveraging digital ecosystems to foster sustainable development and strengthen international market positions.